Weed growth and grain yield in wheat and rice as affected by tillage system and weed management practices in rice-wheat cropping sytem in Bangladesh - S.M. Rezaul Karim (2011)
Rice-wheat (RW)cropping system is an important cropping system in Bangladesh. Crop production on permanent raised beds (PRB)with straw retention is expanding worldwide as a way to increase system productivity and weed management.A 2-years study was conducted at the Regional Research Centre, Rajshahi to compare the effects tillage system ana straw retention (SR)e.g 30% SR of all crops + permanent raised beds (PRB).0%SR + PRB, 30%SR + conventional tillage practice (CTP) and 0%SR + CTP in a intensified RW systems. The effect of herbicides was also evaluated for control. Bed planting lead to higher grain yield both in rice and wheat than conventional planting. The population and dry weight of weeds were less in bed planting than in conventional planting.In both the years the major infested weeds in wheat were :Chenopodium album, Cynodon dactylon, Cyperus rotundus and Lolium spp. In rice the major weeds were Cynodon dactylon, Cyperus rotundus and Cyperus iria. In wheat, Linture 70WG@ 375 g/ha at two leaves stage (10-15 days after seeding (DAS) was most effective in arresting weed growth as compared to 2, 4-D Amine @ 1.5 L/ha at four leave stage (20-25 DAS) and was at par with hand weeding (30-35 DAS). Net profit was also the highest (17320Tk./ha) in Linture 70 WG treated plots and the lowest (14680 Tk./ha)in hand weeded plots